2007
DOI: 10.1086/510609
|View full text |Cite
|
Sign up to set email alerts
|

The Fragmenting Superbubble Associated with the HiiRegion W4

Abstract: New observations at high latitudes above the H ii region W4 show that the structure formerly identified as a chimney candidate, an opening to the Galactic halo, is instead a superbubble in the process of fragmenting and possibly evolving into a chimney. Data at high Galactic latitudes (b > 5 • ) above the W3/W4 star forming region at 1420 and 408 MHz Stokes I (total power) and 1420 MHz

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(91 citation statements)
references
References 33 publications
5
84
2
Order By: Relevance
“…Follow-up Hα observations (Dennison et al 1997) showed that the ionized gas is detected in the periphery of the H i cavity and revealed an enclosed superbubble rather than a chimney, which is sealed at about b = 7 • . As shown by West et al (2007), the appearance of this huge structure seen from the 1.4 GHz radio continuum emission also resembles a closed bubble. We therefore refer to it as "W4 superbubble" in this work.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…Follow-up Hα observations (Dennison et al 1997) showed that the ionized gas is detected in the periphery of the H i cavity and revealed an enclosed superbubble rather than a chimney, which is sealed at about b = 7 • . As shown by West et al (2007), the appearance of this huge structure seen from the 1.4 GHz radio continuum emission also resembles a closed bubble. We therefore refer to it as "W4 superbubble" in this work.…”
Section: Introductionmentioning
confidence: 70%
“…Based on the tight correlation between radio continuum and Hα emission and the flat radio spectrum derived between 408 MHz and 1420 MHz, West et al (2007) conclude that the radio continuum emission from the shells of the W4 superbubble is optically thin thermal emission. We confirmed this by deriving the spectral index from the present data using TT-plots (Turtle et al 1962) between 1.4 GHz and 4.8 GHz.…”
Section: Total Intensity Emission and Spectral Informationmentioning
confidence: 87%
See 2 more Smart Citations
“…Nevertheless, there are very few measurements of magnetic fields in such objects (for another example see West et al 2007). …”
Section: Stellar-wind Bubble In the Anticentrementioning
confidence: 99%